2020
DOI: 10.1111/grs.12306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pasture cover and height on nutrient concentrations in diverse swards in the UK

Abstract: A total of 445 pasture samples were collected from six fields representing a wide range of dry grass content (0–100%), and grass, legume, herb, flower and weed species. Fields were located in the grass‐dominated and temperate regions of western UK and monitored monthly for 9 months during late summer, autumn and winter months. The pasture properties assessed included measurements of percentage of grass content, height (in centimeters), pasture cover (fresh weight (FW) and dry matter (DM) in kg /ha) and pasture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Long intervals between cuts allow for advanced pasture maturity, reflected in increased fibre [11] higher aerial biomass yield. Still, low protein concentration, digestibility and energy [13][14][15], due to wall thickening and reduced cell content [16,17].…”
Section: Of 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Long intervals between cuts allow for advanced pasture maturity, reflected in increased fibre [11] higher aerial biomass yield. Still, low protein concentration, digestibility and energy [13][14][15], due to wall thickening and reduced cell content [16,17].…”
Section: Of 12mentioning
confidence: 99%
“…In addition to pasture management, the climatic characteristics of the time of year also affect the productive performance of the ryegrass-white clover association ( [18][19][20], with ryegrass showing more limitations in its growth during drought events [21] compared to white clover, which thanks to its variability responds with visible phenological changes to new environmental conditions, competing successfully against other plants [22,23]. White clover is characterised by its essential contribution of protein in the diet of animals [16] and by its capacity to fix nitrogen and improve the productivity of this association [23]; however, it has been found that values lower than 20 % of white clover in associated pastures seriously affect these indicators, in addition to restricting the total daily intake of nutrients. The presence of white clover in pastures should not be above 50 % to meet the nutritional requirements of animals and the release of nitrogen to the environment [24,25] For Tilus et al (2022) [11], forage yield increases linearly as the time of cutting is prolonged thus yields have been obtained in this association of 1470 kg DM ha −1 when this is done around 10 cm in height with a remnant greater than 4 cm [6]; 2000 kg DM ha −1 if the height is 13 cm and 2781 kg DM ha −1 if the ryegrass is 29.8 cm [26]; 3974 kg DM ha −1 when the height is 20 cm high and post-grazing remnant of 5 cm [27].…”
Section: Of 12mentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be possible to assess phenological phases of dominating plant species as these are crucial for herbage quality, as has been shown, for instance, in terms of organic matter digestibility. 26 In addition, studies have tried to derive herbage quality estimates from height measurements (e.g., Bell et al 27 ) since providing sufficient high-quality herbage is particularly important for lactating livestock, affecting the animal performance, welfare, and health. 28 However, in cases of non-uniform botanical compositions, the single sward height assessment is probably a poor predictor of herbage quality.…”
Section: Introductionmentioning
confidence: 99%
“…It would also be possible to assess phenological phases of dominating plant species as these are crucial for herbage quality, as has been shown, for instance, in terms of organic matter digestibility 26 . In addition, studies have tried to derive herbage quality estimates from height measurements (e.g., Bell et al 27 28 .…”
Section: Introductionmentioning
confidence: 99%